2012
DOI: 10.1007/s11136-012-0245-0
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year change in self-rated quality of life in a type 1 diabetes population: Wisconsin Epidemiologic Study of Diabetic Retinopathy

Abstract: Purpose To investigate a 10-year change of quality of life and associated factors in a population with type 1 diabetes. Methods The Medical Outcome Study Short Form-36 (SF-36) was administered in participants (n = 520) at the 1995–1996 and 2005–2007 examination phases of the Wisconsin Epidemiologic Study of Diabetic Retinopathy (WESDR). Physical (PCS) and mental (MCS) component summary scores were calculated. The associations between changes of quality of life and demographic, socioeconomic, and clinical fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Several studies have demonstrated that diabetes has a strong negative impact on HRQOL, relative to the general population (Abuawad 2013;Jain et al 2014;Nielsen et al 2016), especially in the presence of complications (Hirai et al 2013;Smith-Palmer et al 2016). Diabetic neuropathy greatly reduces the quality of life in people with DM through increased disability and assuming more hospitalizations than other diabetic complications (Mahmood et al 2009;Tesfaye and Selvarajah 2012;Abuawad 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that diabetes has a strong negative impact on HRQOL, relative to the general population (Abuawad 2013;Jain et al 2014;Nielsen et al 2016), especially in the presence of complications (Hirai et al 2013;Smith-Palmer et al 2016). Diabetic neuropathy greatly reduces the quality of life in people with DM through increased disability and assuming more hospitalizations than other diabetic complications (Mahmood et al 2009;Tesfaye and Selvarajah 2012;Abuawad 2013).…”
Section: Introductionmentioning
confidence: 99%
“…30 A study used 36-Item Short Form Survey (SF-36), showed that PCS score was decreased (p<0.001) and MCS score was increased (p<0.001) after 10 years. 33 A study used 28-item Impact of Vision Impairment (IVI) using multivariable linear model, showed that any DR in unilateral better-eye classifications revealed a 9% reduction in vision related quality of life (VRQoL) compared to individuals with no DR/DME. A significant decrements in VRQoL occurred only when both eyes had either DR or DME (11%).…”
Section: Quality Of Life and Quality Of Life Instrumentsmentioning
confidence: 99%
“…21 Four studies demonstrated decreasing of QoL score as severity increased although not statistically significant. 7,25,33,36 Diabetic retinopathy related comorbidity Diabetic patients with comorbidity had worse QoL. 7,16,18,[20][21][22]25,26,33,35,36 Additional lost in QoL was by increased number of comorbidity, including presence of at least one of comorbidity (minimum ≥1 comorbidities).…”
Section: Severity Of Diabetic Retinopathymentioning
confidence: 99%
See 2 more Smart Citations